Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Problem-Based Learning (PBL) Dengan Pendekatan Deep Learning Pada Materi Ekosistem Kelas X SMAN 1 Rambatan - Ghazi Hanif Ghazali; DWI RINI KURNIA FITRI (Edusainstika, 2026)
Developing teaching materials in the modern era presents new challenges, particularly regarding technology integration and inclusivity. This study developed a student worksheet (LKPD) based on Problem-Based Learning (PBL) and a Deep Learning approach for the topic of ecosystems, employing the Research and Development (R&D) method with the 4D model (Define, Design, Develop, Disseminate). The research subjects consisted of 34 tenth-grade high school students. The results indicate that the PBL-based worksheet incorporating the Deep Learning approach for the ecosystem topic is highly valid, achieving a score of 94%. Practicality test results showed scores of 98% for teachers and 80% for students, corresponding to "highly practical" and "practical" categories, respectively. Thus, the PBL-based worksheet using the Deep Learning approach for the ecosystem topic has proven practical and suitable for supporting biology instruction.